Oral communication skills in english : a study on final semester students of selected programs at UiTM Dungun / Wan Muzlaina Wan Mustafa - Wan Mustafa, Wan Muzlaina (2000)
This is an assessment of Oral Communication skills in English of final semester students of Bachelor of Accountancy (BAcc) and Bachelor of Business Administration (BBA) of Universiti Teknologi MARA (UiTM) Terengganu Campus. The study is solely through the use of Assessment Form (evaluation form). This assessment form was distributed to English lecturers and two different groups of students (BAcc and BBA-Finance) as assessors. The Assessment Form used in this survey was that used by the English lecturers at the Language Center of UiTM in assessing the English Oral Communication skills of students* presentation in all faculties. The findings of the study indicate that, there is a significant difference between lecturers'- and students', assessment on the level of English oral communication skills of BAcc and BBA-Finance students. The result also revealed that, the mean mark of the lecturers and the students are very close to each other for BAcc and BBA-Finance. However, based on the mean mark, range of marks and standard deviation, it can be concluded that BAcc students are in a better position in making a reasoned assessment independent of their own level of English oral communication skills and to assess their own performance in preparing the oral communication skills in the future.